Изменения в содержании свободного пролина в побегах и корнях проростков кукурузы на начальной стадии действия летальных осмотических стрессов - Сергеева, Л.Е.; Михальская, С.И.; Курчий, В.М.; Тищенко, Е.Н. (Фактори експериментальної еволюції організмів, 2014)
Aim. Salt and water stresses essentially decrease viability and productivity of crop plants. There are some biotechnological approaches to raise the level of the stress resistance. The genetic transformation is among them. The procedure of maize Agrobacterium-mediated transformation using LBA 4404 strain with antisense proline dehydrogenase gene suppressor was created and L-390-T0 progeny was obtained. It was necessary to investigate the free proline contents in various plant tissues under normal and stress conditions. Methods. 7-day old corn plants (genotypes L-390 and L-390-T0) were exposed to salinity (2.5% of sea water salts) or water stress (0.8M mannitol) during four hours. The free proline levels in shoots and roots were monitored. Results. In tissues of L-390-T0 plants the free proline levels exceeded these parameters of L-390 plants under both normal and stress conditions. It was shown the particular changes of free proline levels in shoots and roots of 7-day corn plants (genotypes L-390 and L-390-T0) under initial stages of stress pressure of lethal salinity or water stress. The gene of PDH-is the component part of the general genetic system that regulates the proline level under initial stages of lethal osmotic stresses.